MiR-21 Is Remotely Governed by the Commensal Bacteria and Impairs Anti-TB Immunity by Down-Regulating IFN-γ - Yang, Fang; Yang, Yi; Chen, Yiwei; Li, Guobao; Zhang, Guoliang; Chen, Lingming; Zhang, Zhiyi; Mai, Qiongdan; Zeng, Gucheng (Frontiers in Microbiology, 2021)
Tuberculosis (TB) remains a frequent and important infectious disease with a very high burden of morbidity and mortality. Intestinal dysbacteriosis has been implicated in immune response to TB. Recent evidence points out that microRNAs (miRNAs) act at the epicenter of the signaling networks regulating this process. However, the involvement of miRNA in gut microbiota, TB and the host immune system remains unknown. Here we showed that intestinal dysbacteriosis increases the susceptibility to TB and remotely increased the expression of lung miR-21 expression. Systemic antagonism of miR-21 enhanced IFN-γ production and further conferred immune protection against TB. Further molecular experiments indicated that miR-21a-3p could specifically target IFN-γ mRNA. These findings revealed regulatory pathways implicating intestinal dysbacteriosis induced-susceptibility to TB: intestinal dysbiosis→lung miRNA→targeting IFN-γ→impaired anti-TB immunity. This study also suggested that deregulated miRNAs by commensal bacteria could become promising targets as TB therapeutics.